1977
DOI: 10.1111/j.1365-2621.1977.tb12573.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Pungency Due to Capsicum by Gas‐liquid Chromatography

Abstract: A method is described for determining the pungency, due to capsaicinoids, in raw spices, extracts, food and pharmaceutical products by means of GLC. Pure samples of the individual capsaicinoids were prepared and their pungencies determined by ASTA method 21.0 (Scoville Heat Test). The threshold pungency values for these materials are presented. The pure capsaicinoids were used to quantitate the GLC method and identify capsaicinoids found in natural materials. Details concerning sample preparation and silylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 29 publications
4
118
0
2
Order By: Relevance
“…Identification and quantification of the individual capsaicinoids (nordihydrocapsaicin, capsaicin and dihydrocapsaicin) were made by comparing the peak retention time and area with those of an external standard analysed under identical HPLC conditions. 5 Earlier studies with GC 16 and LC 5,17 showed that homocapsaicin and homodihydrocapsaicin were present only at low levels, while norcapsaicin was not found.…”
Section: Resultsmentioning
confidence: 99%
“…Identification and quantification of the individual capsaicinoids (nordihydrocapsaicin, capsaicin and dihydrocapsaicin) were made by comparing the peak retention time and area with those of an external standard analysed under identical HPLC conditions. 5 Earlier studies with GC 16 and LC 5,17 showed that homocapsaicin and homodihydrocapsaicin were present only at low levels, while norcapsaicin was not found.…”
Section: Resultsmentioning
confidence: 99%
“…The total capsaicinoid concentration found in cayenne pepper corresponds to 30 590 Scoville Heat Units (SHU), which express the degree of hot pungency of peppers. [36][37][38] Lipid oxidation Fig 2 shows the TBARS values for all samples thoughout storage, indicative of lipid oxidation. There was a linear increase in TBA numbers of control samples until they reached a maximum value of about 4 at day 12 of storage.…”
Section: Results and Discussion Analysis Of Capsaicinmentioning
confidence: 99%
“…Scoville Heat Units (SHU) were estimated by the method of Todd, Bensinger, and Biftu (1977). The determination of pungency on SHU was accomplished by multiplying the individual capsaicinoid contents by the corresponding value of threshold pungency.…”
Section: Scoville Heat Units Determinationmentioning
confidence: 99%